A. They need to be sure you will be able to pay the loan back
Answer:
The probability that a person with restless leg syndrome has fibromyalgia is 0.183.
Step-by-step explanation:
Denote the events as follows:
<em>F</em> = a person with fibromyalgia
<em>R</em> = a person having restless leg syndrome
The information provided is as follows:
P (R | F) = 0.33
P (R | F') = 0.03
P (F) = 0.02
Consider the tree diagram attached below.
Compute the probability that a person with restless leg syndrome has fibromyalgia as follows:
![P(F|R)=\frac{P(R|F)P(F)}{P(R|F)P(F)+P(R|F')P(F')}](https://tex.z-dn.net/?f=P%28F%7CR%29%3D%5Cfrac%7BP%28R%7CF%29P%28F%29%7D%7BP%28R%7CF%29P%28F%29%2BP%28R%7CF%27%29P%28F%27%29%7D)
![=\frac{(0.33\times 0.02)}{(0.33\times 0.02)+(0.03\times 0.98)}\\\\=\frac{0.0066}{0.0066+0.0294}\\\\=0.183333\\\\\approx 0.183](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%280.33%5Ctimes%200.02%29%7D%7B%280.33%5Ctimes%200.02%29%2B%280.03%5Ctimes%200.98%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B0.0066%7D%7B0.0066%2B0.0294%7D%5C%5C%5C%5C%3D0.183333%5C%5C%5C%5C%5Capprox%200.183)
Thus, the probability that a person with restless leg syndrome has fibromyalgia is 0.183.
answer:
131.88 inches
step-by-step explanation:
- know the formula: 2πr
- now plug in what we have
2πr = circumference
2(21)(3.14)
= 131.88
If
![y=\displaystyle\sum_{n=0}^\infty a_nx^n](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_nx%5En)
then
![y'=\displaystyle\sum_{n=1}^\infty na_nx^{n-1}=\sum_{n=0}^\infty(n+1)a_{n+1}x^n](https://tex.z-dn.net/?f=y%27%3D%5Cdisplaystyle%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20na_nx%5E%7Bn-1%7D%3D%5Csum_%7Bn%3D0%7D%5E%5Cinfty%28n%2B1%29a_%7Bn%2B1%7Dx%5En)
The ODE in terms of these series is
![\displaystyle\sum_{n=0}^\infty(n+1)a_{n+1}x^n+2\sum_{n=0}^\infty a_nx^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%3D0%7D%5E%5Cinfty%28n%2B1%29a_%7Bn%2B1%7Dx%5En%2B2%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_nx%5En%3D0)
![\displaystyle\sum_{n=0}^\infty\bigg(a_{n+1}+2a_n\bigg)x^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%3D0%7D%5E%5Cinfty%5Cbigg%28a_%7Bn%2B1%7D%2B2a_n%5Cbigg%29x%5En%3D0)
![\implies\begin{cases}a_0=y(0)\\(n+1)a_{n+1}=-2a_n&\text{for }n\ge0\end{cases}](https://tex.z-dn.net/?f=%5Cimplies%5Cbegin%7Bcases%7Da_0%3Dy%280%29%5C%5C%28n%2B1%29a_%7Bn%2B1%7D%3D-2a_n%26%5Ctext%7Bfor%20%7Dn%5Cge0%5Cend%7Bcases%7D)
We can solve the recurrence exactly by substitution:
![a_{n+1}=-\dfrac2{n+1}a_n=\dfrac{2^2}{(n+1)n}a_{n-1}=-\dfrac{2^3}{(n+1)n(n-1)}a_{n-2}=\cdots=\dfrac{(-2)^{n+1}}{(n+1)!}a_0](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3D-%5Cdfrac2%7Bn%2B1%7Da_n%3D%5Cdfrac%7B2%5E2%7D%7B%28n%2B1%29n%7Da_%7Bn-1%7D%3D-%5Cdfrac%7B2%5E3%7D%7B%28n%2B1%29n%28n-1%29%7Da_%7Bn-2%7D%3D%5Ccdots%3D%5Cdfrac%7B%28-2%29%5E%7Bn%2B1%7D%7D%7B%28n%2B1%29%21%7Da_0)
![\implies a_n=\dfrac{(-2)^n}{n!}a_0](https://tex.z-dn.net/?f=%5Cimplies%20a_n%3D%5Cdfrac%7B%28-2%29%5En%7D%7Bn%21%7Da_0)
So the ODE has solution
![y(x)=\displaystyle a_0\sum_{n=0}^\infty\frac{(-2x)^n}{n!}](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdisplaystyle%20a_0%5Csum_%7Bn%3D0%7D%5E%5Cinfty%5Cfrac%7B%28-2x%29%5En%7D%7Bn%21%7D)
which you may recognize as the power series of the exponential function. Then
![\boxed{y(x)=a_0e^{-2x}}](https://tex.z-dn.net/?f=%5Cboxed%7By%28x%29%3Da_0e%5E%7B-2x%7D%7D)
Just simplify them to a decimal by dividing the numerator by the denominator.